2017
DOI: 10.1038/s41598-017-13961-5
|View full text |Cite
|
Sign up to set email alerts
|

Energetic mitochondrial failing in vitiligo and possible rescue by cardiolipin

Abstract: Vitiligo is characterized by death or functional defects of epidermal melanocytes through still controversial pathogenic process. Previously, we showed that mitochondria-driven pre-senescent phenotype diminishes the capability of vitiligo melanocytes to cope with stressful stimuli. In the current study, we investigated markers of mitochondrial energy metabolism including the PGC1a axis, and then we determined the index of mitochondrial impairment using a cytomic approach. We found in cultured epidermal vitilig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 65 publications
3
58
1
Order By: Relevance
“…These findings correspond with the observation from individuals with vitiligo—a condition which results in areas of the skin with inactive melanocytes—of reduced energy production in cultured melanocytes with depleted skin pigmentation, compared to healthy melanocytes [55], and the increased presence of vitiligo in patients with genetic mitochondrial dysfunction [56].…”
Section: Pigmentationsupporting
confidence: 87%
“…These findings correspond with the observation from individuals with vitiligo—a condition which results in areas of the skin with inactive melanocytes—of reduced energy production in cultured melanocytes with depleted skin pigmentation, compared to healthy melanocytes [55], and the increased presence of vitiligo in patients with genetic mitochondrial dysfunction [56].…”
Section: Pigmentationsupporting
confidence: 87%
“…However, our findings fail to fully explain the dysregulation of melanocyte biology in vitiligo, especially the dysregulated mitochondrial function of melanocytes 13, 14. Dell'Anna et al have observed increased mitochondria-derived ROS production and impaired activity of electron transport chain complex in vitiligo melanocytes 21. Consistent with their findings, we also detected increased mitochondrial ROS generation, decreased mitochondrial membrane potential, lessened intracellular ATP level and impaired respiratory chain complex activities in melanocytes after H 2 O 2 stimulation, further confirming the involvement of damaged mitochondria in inducing melanocyte destruction in vitiligo.…”
Section: Discussioncontrasting
confidence: 75%
“…Previous studies have demonstrated that the polymorphisms of superoxide dismutase (SOD2), a crucial mitochondrial reactive oxygen species (ROS) scavenger, are genetic risk factors for the susceptibility and the progression of vitiligo 20. Moreover, several lines of evidences have revealed the disordered ultrastructure of mitochondria in vitiligo melanocytes 13, 21, especially the disappearance of cristae, which could impede respiratory chain complex assembly and boost ROS production 22-24, indicating the close linkage between mitochondrial function impairment and melanocyte's susceptibility to oxidative stress. Intriguingly, it is reported that mitochondrial structure is dynamically regulated by two counteracting processes, that are, mitochondrial fusion and fission, with dynamin-related protein 1 (DRP1), fission 1 (Fis1), mitochondrial fission factor (MFF), mitofusin 1 (MFN1), mitofusin 2 (MFN2) and optic atrophy 1 (OPA1) as key regulatory elements 25.…”
Section: Introductionmentioning
confidence: 99%
“…When damage occurs, it may stimulate FAK phosphorylation, thus promoting PGC1α [ 50 ]. Impaired mitochondrial activity raised mitochondrial mass and increased PGC1α and FAK expression [ 51 ]. In the present study, vitiligo skin samples showed phospo-FAK expression stimulation compared to controls.…”
Section: Discussionmentioning
confidence: 99%